Treatment paradigms for ductus arteriosus aneurysms in adults. (August 2014) - Psathas, Emmanouil D; Katsargyris, Athanasios; Lioudaki, Stella; Moris, Demetrios N; Doulaptsis, Mikes; Klonaris, Chris
We report two symptomatic cases of ductus arteriosus aneurysm (DDA) in adults treated in our department over a 5-years period. One patient underwent an open off-pump surgical procedure, while the second one was treated with partial aortic arch debranching and endovascular stent-grafting. DDA in adults is an uncommon condition and can present with rupture, hoarseness or symptoms of airway obstruction. Although indications for intervention are not clearly established, most authors advocate that DDAs should be treated regardless of their size, to avoid the risk of rupture, while others reserve intervention for symptomatic patients. We report on the management of these patients and provide an updated review of the current literature.